Pengaruh Work-Family Conflict Pada Job Satisfaction: Peran Mediasi Emotional Exhaustion Dan Moderasi Emotional Intelligence (Studi Pada Generasi Z Sandwich di START-UP DKI JAKARTA) - Ari Annisa, Prastiti; Sri Runing Sawitri, Hunik (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of work-family conflict on job satisfaction, with emotional exhaustion as a mediator and emotional intelligence as a moderator, among Generation Z sandwich workers in start-up companies in DKI Jakarta. Using a quantitative approach, data were collected from 350 respondents and analyzed with SEM-PLS using SmartPLS 4.0. The results show that work-family conflict negatively affects job satisfaction and positively affects emotional exhaustion. Emotional exhaustion partially mediates the relationship, while emotional intelligence does not moderate the effect of emotional exhaustion on job satisfaction. These findings highlight the importance of managing employee well-being to sustain job satisfaction.